Androgenic overactivation and epigenetic remodeling drive intergenerational toxicity of bisphenol S in zebrafish - Costa, Daniel Fernandes da [UNESP]; Zanardini, Maya; Sanches, Eduardo Antonio [UNESP]; Souza, Ana Regina Seabra de [UNESP]; Rodrigues, Maira da Silva [UNESP]; Moraes, Adriana Carvalho Natal de [UNESP]; Habibi, Hamid R; Nóbrega, Rafael Henrique [UNESP] (Elsevier, 2025)
Bisphenol S (BPS), a widespread plasticizer and endocrine-disrupting compound, can adversely affect steroidogenesis and the hypothalamic-pituitary-gonadal (HPG) axis. This study exposed adult male zebrafish (Danio rerio) to an environmentally relevant BPS concentration (0.5 µg/L) for 14 days (d), assessing its effects on 11-ketotestosterone (11-KT) levels, spermatogenesis, and sperm quality. Additionally, we examined paternal transmission of BPS effects by breeding exposed males with untreated females and evaluating hatching rates, development, survival, and gene expression in offspring. Direct embryonic exposure (0.5 µg/L) was also investigated. BPS exposure increased 11-KT levels in plasma and testes, stimulated meiotic and post-meiotic cysts, and enhanced sperm production. These histomorphometric changes aligned with upregulated expression of sycp3l (meiotic marker), cyp17a1 (androgen synthesis), and genes regulating epigenetic modifications. However, sperm quality was impaired, with reduced motility and fertilization success. In the F1 generation, paternal BPS exposure led to delayed hatching, increased malformations (e.g., absent somites, tail detachment), and higher mortality. In contrast, direct embryonic exposure did not significantly impact development or survival but elevated estrogenic gene expression (esr1, cyp19a1b, vtg1). No estrogenic effects were observed in exposed adults or F1 larvae. Our findings uniquely demonstrate that paternal BPS exposure has greater adverse effects on embryo development and survival than direct embryonic exposure. This study highlights the impact of BPS on hormonal regulation, spermatogenesis, sperm quality, and transgenerational viability, providing new insights into its ecological risks.